An 11-Month-Old Boy with Cherimoya Seed Foreign Body in Bronchus: A Case Report - Warasanti, Endang Susanti (Journal of Diverse Medical Research: Medicosphere, 2024)
Abstract Foreign body aspiration is challenging for ORL-HNS specialists. Not only it can be life-threatening, but also it has unnoticed symptoms for several days, weeks or months, but can cause serious sequelae. This article reports a 11-month-old who was referred to the Emergency Care Unit of RSUD Dr Soetomo Surabaya with chief complaints chest pain after choking  cherimoya seeds 4 hours earlier after eating cherimoya fruit which given by his mother. He coughed continuously and had short of breath and looked cyanosis on his face. Arrived at our hospital, the patient had loss of consciousness, thus we decide to intubate him. From physical examination we found on auscultation examination there were unilateral wheezing and decreased breath sounds on the right side of the lung. From chest X-ray there is no sign of aspiration pneumonia/atelectasis. After stabilize the patient, we decided to undergo extraction and exploration bronchoscopy using a rigid bronschopy and repeated observation to see the progress. Keywords. bronchial foreign body, airway obstruction, aspiration